(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Chronic back pain, which is increasingly common and has a considerable economic impact, is a significant disabling factor. For the past decade, radiofrequency ablation (RFA) is a method that is frequently used to treat many kinds of chronic pain. Therefore, the objective of the current investigation was to determine the long-term clinical outcomes of an RFA. Patients and Methods: Randomized control trail was conducted from March 2019 to December 2021 at Iffat Anwar Medical Complex and department of pain medication Azra Naheed Medical Complex. After taking the written informed consent the patients meeting the inclusion criteria: low back pain for past 2 years, both gender, age > 30 years and failed to respond the previous treatments were enrolled in current study. After radiological assessment total 60 patients were randomized equally into two groups (Group A= Medial Branch Block, Group B= RFA) by using computer generated sequence. The primary outcome of the study was to determine the improvement in low back pain by using visual analog scale and physical impairment by using Oswestry low back disability index scale. Results: A sample of 60 patients were selected. The mean age of the patients was 57.6+9.6 years. 35 (58.3%) of the patients were between 56 and 75 years of age. In the current study, 41 (60.0%) were females, including 21 (51.2%) in Control and 20(48.7%) in intervention group. At 12th (week), one, 1.5, and 2 (years), 30%, 80%, 33.3%, and 90.0% of patients reported a reduction in pain with a significant difference (P-value < 0.05). Conclusion: A significant number of people with lumbar spine pain benefit from effective and long-lasting therapy while using RFA of the lumbar medial branch. Lumbar zygapophysial joints have been subjected to radiofrequency denervation this results in long-term pain relief under normal clinical conditions.